Morphological analysis of colon goblet cells and submucosa in type I diabetic rats submitted to physical training - Remedio, Rafael Neodini [UNESP]; Castellar, Alexandre [UNESP]; Barbosa, Rodrigo Avelaira [UNESP]; Gomes, Ricardo Jose; Caetano, Flávio Henrique [UNESP] (Wiley-Blackwell, 2012)
Colon layers, especially the submucosa, as well as the secretion of goblet cells are extremely important for the functioning and transit of substances in this organ. However, the damages arising from type I diabetes and the effects of physical training, which plays crucial role in the treatment of this disease, are not yet known in these regions. To analyze the changes in colon submucosa and goblet cells of diabetic rats, as well as the effects of physical training, Wistar rats were divided into four groups: sedentary control, trained control, sedentary diabetic (SD), and trained diabetic (TD). The training protocol consisted of swimming for 60 min a day, 5 days per week, during 8 weeks. Colon samples were collected, processed, and evaluated by histochemical and ultrastructural techniques. Goblet and submucosa cells did not show alterations in shape, size, protein and carbohydrate content, in all treatment groups. Decreased amount of collagen fibers, however, was observed in the submucosa and lamina propria of SD rats, but this alteration was recovered in TDs. The ultrastructural analysis, in turn, revealed greater quantity of Golgi apparatus cisterns in SDs, distinctly than TDs, which showed improvement in this diabetic condition. Thus, physical training was responsible for the recovery of some important diabetic alterations, possibly improving the motility of substances in the large intestine. Nevertheless, it cannot be considered alone in the treatment of this disease, requiring the combined practice of other methods. Microsc. Res. Tech. 75:821828, 2012. (C) 2011 Wiley Periodicals, Inc.
Keywords: morphology; diabetes; exercise; large intestine